Centrum i peryferia. Obraz Moskwy w powieści Dmitrija Głuchowskiego Tekst - Zywert, Aleksandra (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2019)
Text is a novel of manners with elements of a thriller, a noir, and a detective novel (but the above-mentioned complementary elements fulfill only a supportive role, because the criminal intrigue exposed at the very beginning is treated marginally amounts to a starting point for deeper considerations of the psychological and sociological nature). Due to the peculiar presentation of the image of the Center (here: Moscow), Text fits into the vision of Moscow as the core of Russian predatory capitalism, exuberant consumerism, glitz, semblance and ruthless struggle for recognition in the ranking of successful people, which is presented in contemporary Russian literature. Its fundamental value is the fact that the realization of the author's idea is mainly due to the confrontation of megalopolis with images of the periphery, which can be regarded as satellite cities of the capital. In his perception of Russia, Glukhovsky is close to Roman Senchin and, similarly to the latter, he believes that the traditionally understood center-periphery, city-village conflict is disappearing, because eventually it turns out that (despite the spatial and social diversity) none of these places (mainly because of conspicuous regressive tendencies) does not give a person a chance for free development and self-realization.